Sport sponsorships: conceptualising employee attitudes, organizational identification and inter-organisational citizenship / Norfazlina Ghazali - Ghazali, Norfazlina (Universiti Teknologi MARA Cawangan Selangor, 2017)
The objective of this research is to explore the nature and prevalence of inter-organisational citizenship behaviours within a sponsorship-rights holder relationship. This research will conceptualise sponsorship as an inter-organisational relationship and investigate how this inter-organisational relationship impacts the employees of sponsors’ organisation. Recent studies emphasize that understanding the mechanics of sports sponsorship is critical to its success. However, there is a lack of research investigating sponsorships as an inter-organisational relationship. This is a gap that would be valuable to fill, because an understanding of inter-organisational relationship principles would assist both sponsors and rights holders to initiate and develop more effective sponsorship relationships. Exploring the phenomenon in Malaysia as the research setting, this study will focus the sponsorship in the football industries in Malaysia.